178k views
3 votes
Solve for x using the Quadratic Formula: x2 − 6x + 9 = 0 x equals negative b plus or minus the square root of b squared minus 4 times a times c, all over 2 times a x = 6 x = 3 x = 1 x = 0

User MGSoto
by
4.5k points

2 Answers

2 votes

Answer:

AH! Quadratic Equations!

Explanation:

So to solve it, let's use Quadratic formula!


x^(2) -6x+9=0

(It can be solved by factoring, but I'm doing what it says)


x=(6+-√(36-36) )/(2) \\x=(6+0)/(2) \\x=3

So, there you go!

NOTE: The Discriminate is 0, so there is only one root(solution) to this problem.

Hope this helps!

P.S. Stay Safe!

User Tonoslfx
by
4.5k points
5 votes

Answer:

x = 3

Explanation:

User Bildsoe
by
4.6k points